2022
DOI: 10.3389/fcvm.2021.775471
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Preoperative Monocyte to High-Density Lipoprotein Ratio on In-hospital and Long-Term Mortality in Patients Undergoing Endovascular Repair for Acute Type B Aortic Dissection

Abstract: Aims: The monocyte to high-density lipoprotein ratio (MHR), a novel marker of inflammation and cardiovascular events, has recently been found to facilitate the diagnosis of acute aortic dissection. This study aimed to assess the association of preoperative MHR with in-hospital and long-term mortality after thoracic endovascular aortic repair (TEVAR) for acute type B aortic dissection (TBAD).Methods: We retrospectively evaluated 637 patients with acute TBAD who underwent TEVAR from a prospectively maintained da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…In the present study, CAD was significantly associated with increased risk of in-hospital MACE in patients with TBAD undergoing TEVAR, which was driven primarily by stroke and limb ischemia. The stroke rate (2.2%) and limb ischemia rate (3.0%) in our study were comparable with that reported in previous studies (24)(25)(26)(27). Furthermore, our study indicated that TBAD patients with CAD significantly had higher rates of CKD and stroke history as well as higher average age than patients without CAD.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, CAD was significantly associated with increased risk of in-hospital MACE in patients with TBAD undergoing TEVAR, which was driven primarily by stroke and limb ischemia. The stroke rate (2.2%) and limb ischemia rate (3.0%) in our study were comparable with that reported in previous studies (24)(25)(26)(27). Furthermore, our study indicated that TBAD patients with CAD significantly had higher rates of CKD and stroke history as well as higher average age than patients without CAD.…”
Section: Discussionsupporting
confidence: 90%
“…6 This study is the first in the literature to investigate the prognostic relationship between MHR and TAAD, yet, MHR has been linked with myocardial infarction as well as bicuspid aortic valve degeneration, proving to be a useful tool in tackling the cardiovascular disease. [6][7][8] Xie et al 9 studied and confirmed MHR as a biomarker for in-hospital and long-term mortality in patients undergoing endovascular repair for acute type b AD. Additionally, Du et al 10 looked at the diagnostic value of MHR in acute AD, providing further evidence in its favor.…”
Section: Discussionmentioning
confidence: 99%
“…e Predictive of postdischarge mortality. ratio, 64,65 and long ncRNAs (e.g., LUCAT1) 66 -have all been suggested and further study in these areas is warranted.…”
Section: Next-generation Biomarkersmentioning
confidence: 99%
“…There seems to be growing evidence for the role of these novel serologic markers in predicting the development of thoracic aortic aneurysm—many of these are elusive based on small sample studies although CRP and transforming growth factor beta appear to be of value 62 . More recently, immunological metrics—such as neutrophil‐lymphocyte ratio (NLR), 63 monocyte to high‐density lipoprotein ratio, 64,65 and long ncRNAs (e.g., LUCAT1) 66 —have all been suggested and further study in these areas is warranted.…”
Section: Future Directionsmentioning
confidence: 99%